Designed materials with the giant magnetocaloric effect near room temperature. (November 2019) - Biswas, Anis; Pathak, Arjun K.; Zarkevich, Nikolai A.; Liu, Xubo; Mudryk, Yaroslav; Balema, Viktor; Johnson, Duane D.; Pecharsky, Vitalij K.
Abstract: The coupling between structural and magnetic degrees of freedom is crucial for realization of interesting physical phenomena associated with magneto-structural transformations resembling austenite-to-martensite transitions. Despite substantial efforts in design and discovery of materials with strong magnetocaloric effects, a majority of viable candidates are composed of non-earth-abundant and toxic elements, while others involve challenging syntheses and post processing. Guided by advanced density functional theory calculations, we report a new family of compounds, i.e., Mn0.5 Fe0.5 NiSi1-x Alx [ x  = 0.045–0.07] exhibiting a giant magnetocaloric effect (MCE) that is tunable near room temperature. Their MCE functionality arises from a distinct magneto-structural transformation between a paramagnetic hexagonal Ni2 In-type phase and ferromagnetic orthorhombic TiNiSi-type phase that can be actuated by magnetic field and/or pressure. As the transition is sensitive to external hydrostatic pressure, the same materials should also exhibit a strong barocaloric response in addition to the giant MCE. Graphical abstract: Image, graphical abstract